Norwegian higher education teachers’ beliefs about teaching, motivation, and approaches to researching and developing teaching - Ferguson, Leila E. (Frontiers in Education, 2025)
Quality teaching in higher education is enjoying renewed political and scholarly interest in Norway. Building on extant research on teachers at primary and secondary levels, and budding research at the tertiary level, the present investigation focuses on higher education teachers’ beliefs about teaching, motivation, and beliefs about researching and developing teaching. Using data from the Teaching in Higher Education (THE) Survey that was subjected to factor and regression analyses, we found that participants (n = 56) preferred alternative and personal sources of teaching knowledge over formal sources and those offered by academic developers. On the whole, the participants were motivated to teach. Relations were found between beliefs about sources of teaching knowledge and motivation, respectively, and beliefs about research and development of teaching. Implications in terms of the Scholarship of Teaching and Learning and academic development, including the need for increased focus on teacher beliefs and evidence-based practice in higher education, are discussed.